Avaliação da qualidade de vida no trabalho no meio ambiente laboral dos servidores técnico-administrativos de uma instituição de ensino superior - Paulino, Rousier dos Santos Dias (2018)
Every worker must have the right to a dignified and balanced working environment, as the environment and the work carried out directly intervene in their quality of life. The work environment is a dimension of the environment and has its legal protection ensured by the Federal Constitution of 1988. The Quality of Life at Work (QLW) is directly influenced by the working conditions and the working environment. This present study aimed to evaluate the QLW of the technical-administrative servers crowded in the year 2018 at the center of Biological and Applied Social Sciences, Campus V – João Pessoa, State University of Paraíba, checking the levels of QLW perceived and the priority aspects for the improvement of the work environment. The research, of descriptive and exploratory character, with quantitative analysis of the data collected from the institution’ servers included the application of the questionnaire proposed by Freitas and Souza (2009) to the evaluation of the QLW of the technicaladministrative servers of college institutions. The questionnaire was composed of 46 closed questions, categorized into eight dimensions, and an empty space. Descriptive statistic was performed for the analysis of the data by using Microsoft Excel and GraphPad Prism v. 6 softwares. Of the 52 technical-administrative servers from the Campus V of the State University of Paraíba, 39 accepted to participate in the research and answered the collected data instrument, providing a reliability index of 95% and a sample error of 7.92%. Questionnaire analysis indicated critical points in the working environment of the Institution that, from the perception of the technical-administrative servers, needed interventions. Items considered as critical priorities are related to Dimension D3 – “Safety and health in working conditions”, regarding to the material resources, environmental conditions of work, periodic health examinations, and protection tools in the execution of the work. In the same way, as the Dimension D4 – “ Constitutionalism”, decisions taken that affect the server and the possibility of reviewing them and privacy within the organization were blamed by the servers; in the same way in Dimension 6 – “Fair and adequate compensation”, were highlighted the benefits, bonuses and salary received by the server; In the same way, in Dimension D7 – “Career opportunity and professional guarantee”, promotions based on the competence and productivity of the server, and investment by the HEI in courses for the training and / or continuity of the server studies; and in Dimension D8 – “Social relevance of work”, the participation of the server in social project coordinated by the HEI in the community. These data, properly contextualized by the management of the HEI may subsidize the planning of actions and interventions which will contribute to improving the quality of life of the servers and the work environment and consequently the service provided to the community.